La fouille du fort Saint-Georges à Chinon (Indre-et-Loire). Premiers résultats - Bruno Dufaÿ (Revue Archéologique du Centre de la France)
This article presents the first results of the excavations undertaken in 2003 and 2004 over almost all of the Fort Saint-Georges at Chinon (Indre-et-Loire), one of three elements of the medieval fortress which dominates the town. The excavation enabled us to clarify the function of the fort, built in the 2nd half of the 12th century at a time when Chinon was the administrative centre of the continental possesions of the Plantagenet King of England. From a military point of view, it formed an advanced fortification protecting the main castle, within a structure that Richard the Lionheart would apply to the Chayeau Gaillard. Inside, some vast buildings made up the dwellings, designed perhaps initially to house the royal chanceller.